Causes and solutions for fruit and vegetable waste: a participatory approach with Romanian farmers for sustainable agriculture - Ruxandra Malina Petrescu-Mag; Dacinia Crina Petrescu; Iulia Ajtai; Carmen Andreea Roba; Oana Adriana Gica; Lucian Cuibus; Ancuta Tenter; Valentin Toader; Adina Letitia Negrusa; Nicoleta Bican-Brișan (International Journal of Agricultural Sustainability)
Fruit and vegetable (FV) waste poses significant challenges to agricultural sustainability, causing resource inefficiencies, environmental degradation, economic loss, and social inequalities. Farmers are the most important stakeholders in minimizing FV waste in primary production, and any intervention must consider their attitudes and perspectives. This study had three objectives: (i) to uncover Romanian farmers’ understanding of FV waste; (ii) to explore their perceptions of direct and indirect causes of FV waste; and (iii) to reveal the solutions suggested by farmers to reduce FV waste. The results of the qualitative research methods, including one to one interviews and a community-based causal analysis (CBCA) process, showed that farmers defined FV waste as discarded produce, excluding items used for compost or animal feed. During the CBCA sessions, three commonly identified indirect causes emerged: consumers’ preference for supermarkets and perfectly shaped FV, the difficulties farmers face in accessing supermarkets, and selling imperfect FV. The study emphasizes farmers’ role in sustainable practices, calling for inclusive policies that prioritize local knowledge and farmers’ needs to tailor FV waste reduction solutions.